Diversity and Conservation of Cave-Dwelling Bats in the Brunca Region of Costa Rica - Deleva, Stanimira (2018)
The Brunca region in Costa Rica contains the largest number of caves in the country, yet the diversity and distribution of bat species within those caves is currently unknown. Without this information, it is not possible to assess changes in populations and assemblages that may indicate severe damages to these critical roosting habitats, and to take evidence-based conservation actions. We present the first study to describe the diversity of cave-dwelling bat species in the Brunca region of Costa Rica in a large number of caves. We collected data of bat species diversity by direct observation and capturing bats inside roosts. Bats were observed in 38 of the 44 surveyed caves, representing 20 species from 4 families, with colony sizes ranging from a few individuals to >7500. In addition, we collected information about the human activities carried out in and around the roosts to assess potential threats that these sites face. Data indicate that caves suffer mostly from unregulated tourist visitation and that one of the most visited caves is also the one with the most species-rich bat assemblages. Our study determined the most important and vulnerable bat roosts in the region and shows the need for urgent conservation actions to protect them.